Keserasian Laki-Laki dan Perempuan: Tawaran Islam terhadap Wacana Feminisme dan Kesetaraan Gender: The Harmony Between Men and Women: An Islamic Perspective on Feminism and Gender Equality - Perdana, Martin Putra; Fauziah, Siti Anne Barkah Nur (Journal of Islamic and Occidental Studies, 2025)
The issues of gender and feminism have recently resurfaced, seemingly as a response to the longstanding discrimination faced by modern women. However, instead of achieving justice and harmony in addressing gender problems, the imposition of gender equality ideology has given rise to new conflicts, particularly in the dynamics of male-female relationships within the family structure. This 'virus' has failed to bring peace and justice; rather, it has sparked various polemics that contribute to moral and value degradation. So how does Islam respond to the issue of gender equality? Using a qualitative approach and employing a library research method, this article aims to present the Islamic perspective on gender equality. Does gender difference always lead to harm, or can these differences actually foster harmony and completeness?